Body Mass Index and Modified Glasgow Prognostic Score Are Useful Predictors of Surgical Site Infection After Spinal Instrumentation Surgery: A Consecutive Series. Issue 3 (1st February 2020) - Kobayashi, Yutaka; Inose, Hiroyuki; Ushio, Shuta; Yuasa, Masato; Hirai, Takashi; Yoshii, Toshitaka; Okawa, Atsushi
Abstract : Study Design: Retrospective observational study. Objective: To analyze a large consecutive cohort of patients who had undergone spinal instrumentation surgery, to characterize a patient population with surgical site infections (SSI), and to identify preoperative risk factors associated with SSI. Summary of Background Data: Malnutrition is a risk factor for SSI in many health conditions; however, the evidence connecting preoperative malnutrition with SSI in spinal instrumentation surgery is limited because of the small number of retrospective studies. While the modified Glasgow prognostic score (mGPS), C-Reactive protein (CRP)–albumin ratio (CAR), controlling nutritional status index (CONUT), prognostic nutritional index (PNI), platelet–lymphocyte ratio (PLR), and neutrophil–lymphocyte ratio (NLR) are established methods for evaluating nutritious status, little has been reported on the predictive value of these indicators with respect to postoperative spinal infection. Methods: We retrospectively investigated 384 patients who underwent spinal instrumentation surgery. We evaluated the significance of risk factors, including mGPS, CAR, CONUT, PNI, PLR, and NLR. We then performed stepwise logistic regression analysis to analyze the concurrent effects of various factors on the prevalence of SSI. Results: Of the 384 patients analyzed, 14 were diagnosed with SSIs. Univariate analysis showed that preoperative BMI, lymphocyte count, albumin, erythrocyte sedimentation rate, CRP, CONUT, mGPS, CAR, and PNI were risk factors for SSI. Stepwise logistic regression analysis revealed that higher mGPS and lower BMI before surgery were independent risk factors for SSI. A receiver operating characteristic curve showed that the cut-off values of mGPS and BMI were 1 and 20.39, respectively. Conclusion: The risk factors for SSI after spinal instrumentation surgery were mGPS more than or equal to 1 and BMI less than or equal to 20.39 kg/m 2 . These findings could help to identify patients at higher risk of SSI after spinal instrumentation surgery. Level of Evidence: 4 Abstract : We investigated whether nutritional status indicators are useful predictors of surgical site infection (SSI). Forward stepwise multivariate logistic regression analysis revealed that body mass index and modified Glasgow prognostic score are significant risk factors for SSI. Therefore, an assessment of nutritional status might be useful for prediction of SSI after spinal instrumentation surgery.